Efficacy and safety of Sacituzumab govitecan in solid tumors: a systematic review and meta-analysis - Yaping Zhang; Jian Chen; Xiaoyan Wang; Hui Wang; Xiaoli Chen; Jianfeng Hong; Hongming Fang (Frontiers in Oncology)
BackgroundSacituzumab govitecan (SG) is an antibody-drug conjugate (ADC) that targets trophoblast cell-surface antigen 2 and is conjugated to SN-38, a potent topoisomerase I inhibitor. SG has demonstrated promising activity against various solid tumors. However, comprehensive evaluations of its efficacy and safety remain limited, and outcomes across studies have shown inconsistency. This systematic review and meta-analysis aimed to assess the therapeutic efficacy and associated adverse events (AEs) of SG in the treatment of solid tumors.MethodsA systematic search of PubMed, Embase, and the Cochrane Library was conducted to identify randomized controlled trials (RCTs) and single-arm studies published up to February 14, 2025. The primary outcomes included overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and treatment-related AEs.ResultsFive RCTs comparing SG with chemotherapy were included in the analysis. SG significantly improved OS (risk ratio [RR] = 0.720; 95% confidence interval [CI]: 0.587–0.882; P = 0.002), PFS (RR = 0.682; 95% CI: 0.516–0.901; P = 0.007), and DCR (RR = 1.286; 95% CI: 1.034–1.599; P = 0.024). However, higher incidences of neutropenia, leukopenia, diarrhea, and anemia were observed in the SG group. In the single-arm meta-analysis, 16 cohorts from five trials were included. The pooled ORR was 21% (95% CI: 16%–27%), DCR was 62% (95% CI: 56%–69%), and the clinical benefit rate was 33% (95% CI: 26%–39%). The median pooled PFS, duration of response, and OS were 4.41 months (95% CI: 3.61–5.22 months), 7.40 months (95% CI: 5.99–8.82 months), and 10.29 months (95% CI: 7.75–12.83 months), respectively.ConclusionAlthough SG demonstrates superior OS, PFS, and DCR compared to chemotherapy in patients with solid tumors, this benefit is accompanied by an increased risk of specific adverse events. Subgroup analyses indicate that SG confers a more substantial clinical benefit in breast and urothelial cancers than in other tumor types.